Restorative Justice dalam Penyelesaian Tindak Pidana Penipuan pada Polres Cirebon Kota - Barlian Mahia Nurwahyu; Ratu Mawar Kartina; Yanti Romlahayati (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the resolution of fraud crimes through restorative justice at the Cirebon City Police Department and the obstacles encountered in its implementation. The study used an empirical juridical method with a qualitative approach through interviews, literature review and documentation. The results indicate that case resolution is carried out through mediation, reconciliation, victim compensation, and termination of investigations based on Police Regulation Number 8 of 2021. Obstacles encountered include investigators' unequal understanding of restorative justice, difficulty obtaining victim consent, limited ability of perpetrators to compensate for losses and complex administrative requirements. Improved investigator training and optimization of mediation mechanisms are needed to support the effectiveness of restorative justice.